2006
DOI: 10.1161/01.atv.0000194097.92824.b3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Strain–Mediated Regulation of Vascular Endothelial Occludin and ZO-1

Abstract: Objective-The vascular endothelium constitutes a highly effective fluid/solute barrier through the regulated apposition of intercellular tight junction complexes. Because endothelium-mediated functions and pathology are driven by hemodynamic forces (cyclic strain and shear stress), we hypothesized a dynamic regulatory link between endothelial tight junction assembly/function and hemodynamic stimuli. We, therefore, examined the effects of cyclic strain on the expression, modification, and function of 2 pivotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…The role of phosphorylation of TJ proteins in the regulation of endothelial TJ integrity has not been studied in detail. In this aspect, some studies showed that tyrosine phosphorylation of endothelial TJ proteins leads to loss of its barrier function (36). In the present study, we, for the first time, report that Src-Pyk2-mediated phosphorylation of ZO-2 results in TJ disassembly and enhances EC permeability in response to 15(S)-HETE.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The role of phosphorylation of TJ proteins in the regulation of endothelial TJ integrity has not been studied in detail. In this aspect, some studies showed that tyrosine phosphorylation of endothelial TJ proteins leads to loss of its barrier function (36). In the present study, we, for the first time, report that Src-Pyk2-mediated phosphorylation of ZO-2 results in TJ disassembly and enhances EC permeability in response to 15(S)-HETE.…”
Section: Discussionsupporting
confidence: 55%
“…1B). Several kinases and phosphatases were reported to regulate the assembly and/or disassembly of TJs via modulation of the phosphorylation state of TJ proteins in epithelial cells as well as ECs (33)(34)(35)(36)(37). Therefore, we next studied the phosphorylation of TJ proteins.…”
Section: (S)-hete Increases Ec Permeability-loss Of Barrier Func-mentioning
confidence: 99%
“…In our model, despite no ischemic signs, cortical compression significantly reduced the size of the cortical microvessels. This may cause the alteration of the blood flow-associated hemodynamic forces such as shear stress and cyclic strain on the vascular endothelium, which have been evidenced to activate integrin and Rac1, to decrease the occludin tyrosine phosphorylation and increase the ZO-1 serine/threonine phosphorylation, and to modulate the expression, association, and distribution of occludin and ZO-1 (Colgan et al, 2007;Collins et al, 2006;Tzima et al, 2002). Moreover, increasing evidences have suggested that the BBB permeability is strictly regulated by the redistribution of tight junction proteins between the cell membrane and the cytoplasmic fraction of endothelial cells, and the underlying mechanism involves the phosphorylation of tyrosine, serine, or threonine in the tight junction proteins (Andras et al, 2007;Elias et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, these studies appear to conflict with our own in vitro findings, which demonstrate that cyclic strain elevates EC barrier function (21) in parallel with MMP-2 and -9 levels (152). This may reflect a hemodynamic balance between MMP induction and barrier upregulation, with the latter favored at physiological levels of mechanical load.…”
Section: Cyclic Strain-mediated Regulation Of Vascular Endothelial Cementioning
confidence: 59%
“…Both models reveal that cyclic strain has a profound impact on endothelial metabolism and can induce qualitative and quantitative changes in gene expression leading to changes in cell fate, with consequences for endothelial phenotype and vessel wall homeostasis (17,111,146). In addition to affecting the expression and/or activation of numerous signaling molecules associated with mechanotransduction, cyclic strain has been shown to regulate the expression and/or activation of several classes of effector genes (and gene products) in vascular ECs, including those regulating 1) vessel diameter: NO, nitric oxide synthase (NOS), cyclooxygenase-2 (COX-2), endothelin (ET)-1, and thimet oligopeptidase (16,20,22,74); 2) proliferation: platelet-derived growth factor (PDGF) and vascular endothelial growth factor (140,169); 3) migration/angiogenesis: Arg-Gly-Asp (RGD)-dependent integrins, urokinase-type plasminogen activator (uPA), plasminogen activator inhibitor (PAI)-1, monocyte chemotactic protein (MCP)-1, MMP-2, MMP-9, and membrane type 1 MMP (MT1-MMP, MMP-14) (150, 152-155, 162, 164); and 4) cell-cell communication/barrier function: intercellular adhesion molecule (ICAM)-1, zonula occludens (ZO)-1, and occludin (21,117).…”
Section: Cyclic Strain and The Vascular Endotheliummentioning
confidence: 99%